Sentinel lymph node in thyroid tumors – own experience - Kaczka, Krzysztof; Luks, Bartłomiej; Jasion, Jakub; Pomorski, Lech (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: To determine the feasibility of sentinel lymph node biopsy (SLNB) for the evaluation of the cervical lymph node status in patients with thyroid tumors. Material and methods : Twenty-three patients with suspected thyroid cancer were enrolled in the study. 0.5–1.0 ml of 1% Patent Blue dye was injected intratumorally. After SLNB, thyroidectomy and proper lymphadenectomy were performed. Results: Sentinel lymph node was detected in 20 (86.9%) patients. Thirty-one SLNs were found – 21 (67.7%) were located in the central neck compartment, 4 (12.9%) in the lateral neck compartment, 6 (19.4%) in the upper mediastinum. The number of SLNs ranged from 1 to 3 (mean 1.6). Sentinel lymph node was positive in 5 (25%) patients, negative in 15 (75%) in the final histopathology. Sentinel lymph nodes were located only in the central neck compartment in 13 patients, and in both the central and lateral neck compartments in 2 patients. In one patient, SLNs were located only in the central neck compartment and upper mediastinum. Three patients had SLNs only in the upper mediastinum, while one had them only in the lateral neck compartment. In one patient a node regarded as SLN was negative, while there were metastases in removed non-sentinel lymph nodes (NSLNs). In two patients, histopathology of SLNs showed that they were actually parathyroid glands. Conclusions : Our results confirm that thyroid cancer SLNB is rather easy to carry out. Its performance along with intraoperative examination can help to avoid unnecessary lymphadenectomy. However, it should be kept in mind that parathyroid glands can be stained and removed by mistake during SLNB.